(untitled) (Biological Sciences - PJSIR, 2008)
Okra (Abelmoschus esculentus L) pods were stored at the relative humidity of 90% and 100% for up to 10 days. The moisture content, crude fibre, and protein, fat, viscosity, hydrolysable and condensed tannin, total phenol, vitamin C and reducing power of the okra were determined on alternate days. Okra pods stored at 100%RH experi- enced the least percentage loss in all the determined parameters though the loss of antinutrient was lower at this relative humidity.